171. Impact of Limiting Antimicrobial Indication Options in a Pediatric Electronic Health Record. (26th November 2018) - Shapiro, Craig; Chan, Shannon; Ravin, Karen
Abstract: Background: In April 2005, our Antimicrobial Stewardship Program (ASP) started to require prescribers to select an indication as part of an antimicrobial (AM) order. The ASP developed a list of approved indications for each AM with an unlimited number of options including "other." In 2015–2016, we modified the indication lists to decrease the number of options. The goal of this project is to compare the frequency of indication "other" and the appropriateness of provider-selected indications before and after the intervention. Methods: We performed a retrospective cohort study of cefepime, ceftriaxone, piperacillin/tazobactam, and ciprofloxacin (IV) orders for all children in our facility excluding orders placed in ambulatory locations and the emergency department. AM orders and provider-selected indications from January to March 2014 (preintervention) and 2017 (postintervention) were compared. Chart review was performed on a sample of pre- and postmodification orders to assess the appropriateness of provider-selected indications. An indication was considered appropriate if the provider-selected indication matched the clinical indication documented. Results: A total of 747 orders were included in the data analysis, 350 and 397 orders from pre- and postintervention period, respectively. Ceftriaxone was the most commonly prescribed AM:13.7 and 17.2 orders per 1, 000 inpatients-days during pre- and postintervention periods. The percent of indication "other" orders increased in the postintervention period for ceftriaxone while it decreased for ciprofloxacin and remained about the same for cefepime and piperacillin/tazobactam. Most prescribers who selected indication "other" for ceftriaxone during the postintervention period did not provide a reason (29.8%). The agreement between clinical and provider-selected indications was consistent in pre- and postintervention period except piperacillin/tazobactam (RR = 0.56). Conclusion: Requiring selection of an indication encourages prescribers to evaluate their rationale for initiating an AM. Decreasing the number of indication options for some AMs was associated with increased use of indication "other, " suggesting that the prescriber could not find an indication that matched their needs. Disclosures: All authors: No reported disclosures.